The Effectiveness of Cognitive Behavioral Therapy to Improve Resilience of Frog Troop Command School Students in Kodiklatal: Efektifitas Cognitive Behavior Therapy Untuk Meningkatkan Resiliensi Siswa Sekolah Komando Pasukan Katak Di Kodiklatal - Sulistiono, Andy (Universitas Muhammadiyah Sidoarjo, 2020)
The Indonesian Navy's Frog Troop Command Soldiers are special personnel designed to deal with difficult situations and special naval warfare missions. The dynamics of forming as a candidate for Kopaska personnel and the pressure of education at the Frog Troop Command School were so heavy that some students were unable to adapt well, stressed and lacked confidence, so they were unable to continue their education. Resilience is the ability of each individual to cope and adapt to problems that occur in life. Resilience is needed by students to be able to survive while carrying out education at the Frog Troop Command School. Several studies have found that resilience can be increased by using a Cognitive Behavior Therapy approach. This study aims to determine the effectiveness of the CBT intervention on increasing resilience in the Frog Troop Command School students. The use of the CBT method is expected to be able to increase the resilience of students when under pressure during education at the Frog Troop Command School. Therefore, in order to increase the readiness of students to face the heavy educational pressures and stress that arises during their education at the Frog Troop Command School, it is necessary to know how the use of this CBT method and its effect on them. This therapy session intends to explore the use of the CBT method to control oneself in order to be able to face the pressures of education at the Frog Troop Command School